Environmental Risk Factors and Behaviors Towards Malaria in the Working Area of Banyuasin Purworejo Health Center - Nur Fajria Safarina, Ismi; Joko, Tri; Budiyono, Budiyono (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
In 2021, the Banyuasin Health Center's area in Purworejo reported 143 malaria cases, which decreased to 33 cases in 2022. To understand the factors influencing malaria transmission, a case-control study was conducted. The study focused on environmental and behavioral risks within the health center's jurisdiction. The case group included 33 individuals who had malaria in 2022, while the control group comprised 33 individuals without malaria, matched by sex and age. Data was collected through questionnaires, interviews, and observations using Chi-square analysis with a 5% significance level and 95% confidence interval. Significant risk factors identified included the presence of puddles (OR 4.808, 95% CI 1.667–13.862), absence of wire netting on ventilation (OR 4.713, 95% CI 1.341–16.566), not using mosquito nets (OR 7.429, 95% CI 2.461–22.422), not using mosquito repellents (OR 6.042, 95% CI 1.731–21.086), and not wearing tight clothes (OR 5.714, 95% CI 1.925–16.965). Conversely, the absence of a ceiling (OR 3.444, 95% CI 0.641–18.508), absence of cattle (OR 0.320, 95% CI 0.116–0.883), and absence of bushes (OR 2.692, 95% CI 0.631–11.488) were not significant factors. In conclusion, the study highlighted that stagnant water, poor ventilation measures, and inadequate personal protection contribute significantly to malaria risk in the Banyuasin Health Center's area. Improving housing conditions and promoting the use of mosquito nets and repellents are crucial in mitigating malaria transmission effectively in this region of Purworejo.